Perbandingan Model Group Investigation dan Number Head Together: Analisis terhadap Hasil Belajar - Shofiul Hakim; Effendi Effendi; Widayanti Widayanti (Pendidikan Fisika Universitas Nurul Huda, 2020)
The aim of this study was to analyze the effect of the Model Group Investigation model and the Number Head Together model on learning outcomes. Quasi-experimental method used in this research, the instrument used is multiple choice questions that produce research data. Research data were analyzed using t-test. The results showed that the Group Investigation model and the Number Head Together model could improve learning outcomes. In the result, the class that used the Group Investigation model had a higher score than the class that used the Number Head Together model. For further research, it is necessary to apply a model integrated with interactive multimedia, so that, it will be more interesting and can motivate students in learning.